Students’ Perception on Using Storytelling in Developing Socio-Cultural Competence - Genta Sakti; Eliza Eliza; Veni Roza; Absharini Kardena (Lingua Cultura, 2023)
The research aimed at finding out students’ perception of using storytelling as one of the techniques used in English class in order to develop students’ sociocultural competence. The research was conducted under mixed-method research. The sample of the research was English students at IAIN Bukittinggi who had taken storytelling classes and English students at UIN Imam Bonjol Padang who had joined an English activity (storytelling) held by the English students association of English study program. Data collection was done by distributing questionnarires and conducting interview. The instruments of the research were a questionnaire and an interview guide. The data were analyzed using quantitative analysis for the data from the questionnaire and qualitative analysis for the data from the interview. The research finding shows that the students agree that they have improved their ability in sociocultural competence, at least in five aspects. They state that they are good in these five elements; (1) students’ attitude toward sociocultural competence, (2) students’ knowledge of sociocultural competence, (3) students’ ability to interpret and relate cultural issues, (4) students’ ability in discovery and interaction, and (5) students’ ability of critical cultural awareness. Thus, it can be stated that storytelling is a good technique that can be used to develop students’ sociocultural competence based on students’ perceptions.